Correlations between instructor's caring behavior and nursing students' caring behavior: an international study - Leodoro J. Labrague; Konstantinos Tsaras; Denise M. McEnroe - Petitte; Olaide B. Edet; Jawaher Bin Jumah; Shreedevi Balachandran; Judie Arulappan; Simon Macharia Kamau; Ioanna V. Papathanasiou (Ene, 2016)
Introduction: Theoretically, caring relationship between faculty - student generates a caring moment. However, there is a scarcity of empirical evidence about how caring interactions with faculty can enhance students' caring outcomes. Aim: The aim of this study was to identify the levels of students' and instructors' caring behavior and to explore the correlations between instructors' and students' caring behavior. Methods: A descriptive, non - experimental design has been used in this study. Data collection was based on interviews using two standardized questionnaires; the Nursing Students' Perception of Instructor Caring (NSPIC) and the Caring Behavior Inventory (CBI). Respondents were consisting of nursing students from identified schools and colleges of nursing in different countries. Data were analyzed with SPSS version 21.0. Results: The sample was consisted of 368 nursing students (91% female, 9% male) from seven countries (26% Philippines, 31.5% Greece, 1% Kenya, 0.5 Oman, 35.5% India, 5% Nigeria, 0.5% Saudi Arabia). Forty two percent of students are in the second year of studies, 13% in the third year and 45% in the fourth year. The mean score of NSPIC was 4.02±0.30 and the mean of CBI was4.56±0.13. The mean for each factor of NSPIC was 4.39±0.13 for the factor "instills confidence through caring", 3.92±0.212 for "supportive learning climate", 4.06±0.06 for "appreciation of life's meaning", 3.66±0.11 for "control versus flexibility" and 4.01±0.48 for "respectful sharing". The mean for each factor of CBI was 4.63±0.11 for the factor "assurance", 4.58±0.06 for "knowledge and skills", 4.55±0.18 for "respectful" and 4.47±0.14 for "connectedness". Correlation analysis showed statistically significance between relevant variables. Conclusions: Instructors' caring behavior affects nursing students' caring behavior. Through positive faculty modeling and role modeling, nursing students can be professionally trained to develop the competence of caring.